Current Practices of Railway Ballastless Track Design Methods in China - Peng Chen; Chen Hua; Haiyan Han; Hanbing Xiao; Xinghan Liu; Yanglong Zhong (Applied Sciences)
With the development of railway transportation, diversified demands for track structures require the design methods to be safer, more flexible and efficient. At present, the limit state method is regarded as a more scientific design method compared to the allowable stress method, but its optimization effects await further research. Taking a new type of prefabricated track slab as an example, the differences between the two methods are deeply analyzed using finite element simulation and formula calculation. The development prospect for the track design methods is proposed, providing reference for new structures. The results show the following: (1) There are significant differences in the calculation principles between the two methods. Unlike the single safety factor K of the allowable stress method, the partial factors of the limit state method make it more reasonable. (2) The working conditions of different train speeds and temperature gradients are the main factors influencing the design results, and the latter plays a main control role. (3) Under current specification, the reinforcement and slab thickness can be reduced by approximately 6.5% and 3.4%, respectively, according to the limit state method, but the values its coefficient still need to be studied further to achieve efficiency.